Optical coherence tomography analysis of bioresorbable vascular scaffolds in comparison with metallic stents: A core lab perspective - Yohei Sotomi (2018)
© 2017 by Taylor & Francis Group, LLC. The implantation of a bioresorbable scaffolds (BRSs) is a new approach that provides transient vessel support with drug delivery capability, potentially without the limitations of permanent metallic implants [1]. The potential short- and long-term performance of this technology has been repeatedly investigated with optical coherence tomography (OCT) [2-7]. However, images acquired by OCT after implantation of BRSs are different from those with metallic stents due to the translucency of polymeric materials compared to the opacity of metallic compounds (Figure 5.3.1). Metallic struts appear on OCT as a reflective leading structure with abluminal shadowing, while polymeric struts appear as a “black box” area surrounded by bright reflecting frames without abluminal shadowing. As a consequence, in polymeric scaffolds the vessel wall behind the struts and the luminal area can easily be imaged and assessed, contributing to several advantages in quantitative analysis: (1) capability of measuring the lumen vessel wall interface at baseline; (2) accurate assessment of malapposed struts; (3) measurement of strut/strut core area; (4) precise measurements of flow area; and (5) measurement of neointimal area between and on top of the struts.